"Precolumbian Moulages" Huacos, Mummies and Photographs in the International Controversy over Precolumbian Diseases, 1894-1910 - Farro, Máximo Ezequiel (2015)
By the late nineteenth century an international controversy arose referred to the probable existence of certain diseases such as leprosy, syphilis and lupus in pre-Columbian America. Led by the American physician Albert Sidney Ashmead (1850-1911), it brought together scholars from Europe and the Americas. In this context, certain types of Peruvian archaeological pottery and mummies, along with series of photographs illustrating the effects of these diseases in contemporary patients, met a prominent role as comparative evidence. In this article we analyze how this type of collections were used as evidence in the debates about pathologies of the past, an issue that from a historical standpoint have received considerably little attention.